1985
DOI: 10.1104/pp.77.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the K+-Stimulated ATPase of the Plasmalemma of Pinto Bean Leaves by Ozone

Abstract: MATERIALS AND METHODSThree varieties of Phaseolus vulgaris which differ in their sensitivity to ozone were examined for changes in some physiological and structural plasma membrane characteristics. Plasma membrane vesicles were prepared from control and ozone-treated (0.2 to 0.5 microliters per liter ozone for 5 hours) leaf tissue, and the (K' + Mg2')-ATPase activity determined and compared. No major changes were observed in the resistant varieties. The sensitive variety showed a severe inhibition of ATPase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
29
0

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 12 publications
5
29
0
Order By: Relevance
“…Exposure of fir and spruce to a combination of both gases gave a higher response of the antioxidants than exposure to each pollutant alone. But, because of the low potency of 03, the pollutant seems not to be the dominator in 03 + S02 action as recently proposed by Olszyk and Tingey (12 (3). In our studies, increase of antioxidants was a general response to air pollutant action.…”
Section: Resultssupporting
confidence: 51%
“…Exposure of fir and spruce to a combination of both gases gave a higher response of the antioxidants than exposure to each pollutant alone. But, because of the low potency of 03, the pollutant seems not to be the dominator in 03 + S02 action as recently proposed by Olszyk and Tingey (12 (3). In our studies, increase of antioxidants was a general response to air pollutant action.…”
Section: Resultssupporting
confidence: 51%
“…Tingey & Taylor (1982) reported that SH concentration of crude foliar extracts of spinach (Spinacia oleracea), bean (Phaseolus vulgaris) and tobacco (Nicotiana tabacum) became smaller after exposure to O $ by the formation of disulphide bonds. In a sensitive variety of common bean, Dominy & Heath (1985) observed severe ozone-induced inhibition of plasmalemma ATPase activity, which could be reversed by treatment with sulphydryl compounds. They concluded that the inactivation was caused by the oxidation of a protein sulphydryl to a disulphide bridge and that sulphydryls can repair ozone-damaged plasmalemma proteins.…”
Section: mentioning
confidence: 96%
“…There is indirect evidence that O 3 affects the plant plasma membrane because altered membrane permeability and ion leakage are frequently detected in leaves and in the unicellular alga Chlorella sorokiniana after treatment with the gas (11). Little research has been performed on the underlying mechanisms, although two studies have demonstrated that membrane vesicles isolated from leaves of O 3 -treated pinto bean (Phaseolus vulgaris L. var Pinto) plants display altered Ca 2ϩ transport (12) and a decrease in K ϩ -stimulated ATPase activity (13). However, all of these studies lack specificity with regard to cell type and involvement of molecularly defined transport molecules.…”
mentioning
confidence: 99%